The Application Of Encryption And Decryption To The Delivery Of Text Messages Using The Rc4 Algorithm (Rivest Code 4) Utilizes The Lsb (Least Of Significant Bit) Algorithm As An Insertion Into The Image - Al Boy In; Achmad Fauzi; Hermansyah Sembiring (International Journal of Health Engineering and Technology, 2022)
The use of image media information has several disadvantages, one of which is that it is easy to manipulate by certain parties with the help of technology that is developing today. Efforts that can be made in improving the security of the transmission of image information are cryptography, which is the science and art of keeping messages safe. In this study, the RC4 (Rivest Code 4) and LSB (Least Of Significant Bit) stegnography methods were applied which aimed to obtain a stronger cipher by inserting messages into the image so that it was difficult to intercept. RC4 (Rivest Code 4) algorithm for encrypting and decryption, LSB (Least Of Significant Bit) stegnography used to decode and decode images. The results of this study show that by applying RC4 (Rivest Code 4) and LSB Stegnography (Least Of Significant Bit) can secure messages inserted into the image and secure keys for data needs. The encoding and decoding process time is influenced by the number of messages that will be kept secret.